Pattern of Tibial Shaft Fractures in Universal College of Medical Sciences, Bhairahawa: A Review of Sixty Cases - Baral, R; Khan, JA; Singh, GP (Journal of Universal College of Medical Sciences, 2013)
BACKGROUND: Tibia is one of the commonest long bone fracture seen in emergency. Road traffic accidents are the major causes of fracture shaft of tibia. However, studies on these fracture have not been conducted in this part of the world so we conducted this study to identify epidemiological characteristics (age, sex, mechanism of injury, season, source of injury, type of fracture. any associated injury, location, method of treatment and complication) in patients with fracture shaft of tibia admitted in the emergency of Medical College hospital, Bhairahawa. METHODS: This is hospital based prospective observational study conducted at Universal College of Medical Science Teaching Hospital, Bhairahawa (Lumbini zone) among 60 tibial shaft fracture patients in hospital emergency. The study period was from December 2010 to November 2011. RESULTS: All total of 60 tibial shaft fracture in 60 patients with a mean age of 28.35 yrs(3-75yrs) were reviewed. The cause of injury were mostly road traffic accident of which Bike (26.6%,), Bus (6.7%), Car (6.7%), Cycle (10%), Rickshaw (6%), Tractor (6.7%), Truck (1.7%), and Vehicle collision (3.3%) were more prevalent. Other injuries were Bomb blast (1.7%), Fall injury (16.7%), Logroll (3.3%), Sports/football (5.5%) and Stone injury (1.7%) . Distal one third of tibial shaft (49.2%) was the commonest site of fracture. Most of the patients presented between 1st hour to even 10 days of injury. Sixty five percent of the fracture were closed and 35% were open. Most were managed operatively (51.7%). Mean time for union of close type of fracture was 13.78(SD ±2.99) weeks and for open was 16.2 weeks (SD±3.34). Complication included infection in one patient and delayed union in two patients. CONCLUSION: In our present study, most tibial shaft fracture were due to road traffic accident. So, efforts should be made by concerned authorities for improving the roadways system of Nepal as well as provision of standard but affordable health care for victims of road traffic crashes. DOI: http://dx.doi.org/10.3126/jucms.v1i3.8773 Journal of Universal College of Medical Sciences Vol.1(3) 2013: 11-14